Licofelone-A Novel Analgesic and Anti-Inflammatory Agent - Kulkarni, S. K.; Pal Singh, Vijay (Current Topics in Medicinal Chemistry, 2007)
Dual inhibitors that block both cyclooxygenase (COX) and lipoxygenase (LOX) metabolic pathways of arachidonic acid are expected to possess clinical advantages over the selective inhibitors of COX enzyme. One of the most promising compounds belonging to this category is licofelone ([2,2 -dimethyl -6-(4-chloropheny-7-phenyl-2,3-dihydro- 1H-pyrrazoline-5-yl] acetic acid). Originally discovered by Merckle GmbH and developed by EuroAllaince, licofelone (IC50 COX=0.21 μM, IC50 5-LOX=0.18μM) possesses significant analgesic, anti-inflammatory, and antiasthmatic effects at doses that cause no gastrointestinal (GI) side effects. The pharmacodynamic profile of licofelone has been assessed and compared with widely used NSAIDs in different animal models. The ED50 value of licofelone is reported to be 11.22- 27.07 mg/kg, po and 39.5-55-8 mg/kg, po against carrageenan-induced paw oedema and Randal Selitto hyperalgesic assay in rats, respectively. Licofelone showed analgesic effect (ED50 = 31.33 mg/kg) against acetic acid-induced writhing in mice. Licofelone has long duration of action and more effective than indomethacin and zileuton with ED50 values of 2.92 mg/kg, po and 36.77 mg/kg, po, in the mechanical hyperalgesia and cold allodynia testing, respectively, against rat model of incisional pain. Licofelone significantly ameliorated indomethacin-induced gastric ulceration, neutrophil adhesion in mesentery, and lipid peroxides in rat gastric mucosa. Also, licofelone reversed the altered vascular permeability, morphological changes, and prevented NSAIDs-related increase in leukotriene levels in gastric mucosa. The preclinical studies have shown that licofelone not only has convincing pharmacodynamic effect but also it is well tolerated. It is currently under clinical evaluation in osteoarthritis (OA), the most common form of arthritis. The present review describes pharmacological and clinical development of licofelone as a dual inhibitor.
Keywords: Licofelone